The Role of Policies in Supporting the Development of Marine Logistics Industry Clusters - Mohammed Riadh (Collaborate, 2024)
The maritime logistics industry cluster plays an important role in supporting global trade and international supply chains. The development of this industrial cluster can provide significant economic benefits, such as increased productivity, innovation and competitiveness. However, the formation and growth of the maritime logistics industry cluster does not occur automatically and requires government policy support. This research aims to explore the role of government policy in supporting the development of the maritime logistics industry cluster. The research methods used include literature studies, policy analysis, case studies, surveys, and data triangulation. The research results identify various policy instruments that can be used by the government, such as infrastructure development, fiscal incentives, supportive regulations, human resource training programs, investment promotion, and collaboration between stakeholders. However, policy implementation also faces challenges such as coordination between stakeholders, prioritization of infrastructure investment, development of skilled human resources, and an effective regulatory framework. The recommendations put forward include increasing coordination between stakeholders, targeted infrastructure investment, human resource training and education programs, and strengthening the regulatory framework. This research provides valuable insights for policy makers, industry players, academics and other stakeholders in efforts to develop a strong and sustainable maritime logistics industry cluster.